2020
DOI: 10.2478/raon-2020-0056
|View full text |Cite
|
Sign up to set email alerts
|

Completely resected stage III melanoma controversy - 15 years of national tertiary centre experience

Abstract: BackgroundTwo prospective randomized studies analysing cutaneous melanoma (CM) patients with sentinel lymph node (SLN) metastases and rapid development of systemic adjuvant therapy have changed our approach to stage III CM treatment. The aim of this study was to compare results of retrospective survival analysis of stage III CM patients’ treatment from Slovenian national CM register to leading international clinical guidelines.Patients and methodsSince 2000, all Slovenian CM patients with primary tumour ≥ TIb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Since osteosarcoma (OS) has a high incidence of recurrence and metastasis, therefore, intensive research has been focused on the mechanisms underlying its metastasis and invasion [16][17][18][19]. In this study, we frst showed that caudatin could restrain the malignant phenotypes of OS cells by inhibiting cell proliferation, inducing apoptosis, and impairing cellular glycolysis.…”
Section: Discussionmentioning
confidence: 97%
“…Since osteosarcoma (OS) has a high incidence of recurrence and metastasis, therefore, intensive research has been focused on the mechanisms underlying its metastasis and invasion [16][17][18][19]. In this study, we frst showed that caudatin could restrain the malignant phenotypes of OS cells by inhibiting cell proliferation, inducing apoptosis, and impairing cellular glycolysis.…”
Section: Discussionmentioning
confidence: 97%